1389. A Comparison of a Telephone versus In-Person HIV Linkage to Care Intervention in a Large Health Care System. (15th December 2022) - Leonard, Michael; Polk, Christopher; Zhao, Jing; Zhao, Jing; Zhao, Jing; Hetherington, Timothy; Gohs, Frank; McCurdy, Lewis
Abstract: Background: Evidence suggests linkage to care (LTC) should occur immediately after HIV diagnosis improves retention in care and viral suppression. Established protocol for newly diagnosed or out of care people living with HIV (PLwH) with hospital admission in our healthcare system is for an in person LTC encounter for outpatient care including clinic follow up. We compared whether an in-person versus phone encounter intervention, were equally effective LTC methods. Methods: PLwH admitted to any of three hospitals in our vertically integrated healthcare system were identified through the electronic health record (EHR) daily by the LTC coordinator for further screening. Inclusion criteria included: inpatient status with ICD9/10 code in EHR for HIV, no self-reported combination anti-retroviral therapy (cART) in the 30 days prior to admission, and not engaged in HIV care in greater than 12 months. Patients were randomized to either an in-person visit or a phone-call LTC encounter. Primary outcomes included follow up with an HIV provider within 30 days of discharge, and cART prescription 90 days of being discharged. Viral load suppression, CD4 count and readmission rates were secondary outcomes. Results were analyzed using an intent to treat model. All tests were two-sided at the significance level of 0.05 Results: 2750 patients were screened for eligibility, 260 randomized during an 18-month period to an in-person visit (n=131) or telephone visit (n=129). The median age was 45 years, 67% were male, and 78% Black/African American. 15% of patients were newly diagnosed during admission. (Table 1) No differences were observed between the two LTC groups in follow up within 30 days (41% total), cART prescription within 90 days (76%), viral load suppression at 6 months (45%), CD4 count (57%), and readmission within 30 days of discharge (34%). (Table 2). Conclusion: Telephone and in-person encounters for LTC had similar outcomes regarding HIV follow up, ART prescribing, viral suppression, and hospital readmission at our institution. Improvements in the linkage process do need to be made in all outcome categories to further improve care with and ultimately viral suppression. Telephone visits provide opportunity to make LTC more efficient and with less human resource needs. Disclosures: Christopher Polk, MD, Gilead: Advisor/Consultant.